2012
DOI: 10.1089/thy.2011.0123
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Patterns and Novel Mutations of the BRAF Gene in a Large Cohort of Korean Patients with Papillary Thyroid Carcinoma

Abstract: Out of 1041 Korean patients with PTC, 0.4% had rare types of BRAF mutation and three new somatic mutations were identified. The BRAF mutation rate was quite low in PTC with follicular morphology regardless of tumor size. However, the prevalence of BRAF mutation in microcarcinoma and follicular variants of PTC is relatively high in Korea and its analysis may be clinically useful for managing the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…Among those, the most common mutation is a point mutation that involves a thymine to adenine substitution at position c.1799 of the BRAF gene, which results in a valine-to-glutamate substitution at amino acid codon 600 (p.Val600Glu; V600E). BRAF V600E represents almost 99% of all BRAF mutations in thyroid cancer (2). We previously reported that BRAF mutations were found in 835 (80.2%) of 1,041 Korean patients with PTC (2).…”
Section: Introductionmentioning
confidence: 99%
“…Among those, the most common mutation is a point mutation that involves a thymine to adenine substitution at position c.1799 of the BRAF gene, which results in a valine-to-glutamate substitution at amino acid codon 600 (p.Val600Glu; V600E). BRAF V600E represents almost 99% of all BRAF mutations in thyroid cancer (2). We previously reported that BRAF mutations were found in 835 (80.2%) of 1,041 Korean patients with PTC (2).…”
Section: Introductionmentioning
confidence: 99%
“…BRAF mutations are the most common mutations in PTCs, and BRAF V600E constitutes 99% of all BRAF mutations 37. The increase in prevalence of BRAF mutations in accordance with iodine supplementation and increase in proportion of PTCs have been reported in different geographical areas 38, 39, 40.…”
Section: Discussionmentioning
confidence: 98%
“…Finkelstein et al21 demonstrated a significant association between the presence of the BRAF mutation and fibrosis, desmoplastic stromal reaction, and infiltrating tumor borders. The BRAF mutation occurs commonly in Korean patients with PTC, ranging in frequency from 52% to 87% of all cases 8. The prevalence of the BRAF mutation worldwide is reported to be as high as 80% to 100% in TCVPTCs 29.…”
Section: Discussionmentioning
confidence: 99%
“…The tissue sections were manually microdissected to enrich for tumor cells. We screened for mutations in exon 15 of the BRAF gene using polymerase chain reaction amplification and direct DNA sequencing, as described previously 8,22…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation